2023
DOI: 10.26603/001c.68143
|View full text |Cite
|
Sign up to set email alerts
|

Novel Orthobiologic Preparation and Regenerative Rehabilitation of a Complex Shoulder Injury in a Competitive Adolescent Female Athlete

Abstract: Background Platelet-rich plasma (PRP) and prolotherapy have resulted in promising outcomes in patients with various types of shoulder injuries. However, there is a lack of preliminary evidence supporting preparation of PRP production, timely application of these therapies and regenerative rehabilitation protocols. The purpose of this case report is to describe the distinct method including orthobiologic preparation, tissue-specific treatment and regenerative rehabilitation of an athlete with a complex shoulder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Prolotherapy resulted in successful outcomes such as pain, disability, a full return to sport, and regenerative tissue healing in athletes, even if further and more consistent studies have to be realized. 49…”
Section: Prolotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Prolotherapy resulted in successful outcomes such as pain, disability, a full return to sport, and regenerative tissue healing in athletes, even if further and more consistent studies have to be realized. 49…”
Section: Prolotherapymentioning
confidence: 99%
“…In a retrospective case-control study, Lee et al 48 demonstrated dextrose prolotherapy improved pain, disability, isometric strength, and shoulder active range of motion in patients with refractory chronic nontraumatic rotator cuff disease. Prolotherapy resulted in successful outcomes such as pain, disability, a full return to sport, and regenerative tissue healing in athletes, even if further and more consistent studies have to be realized 49 …”
Section: Regenerative Medicinementioning
confidence: 99%